Orally Administered Lycopene Attenuates Diethylnitrosamine-Induced Hepatocarcinogenesis in Rats by Modulating Nrf-2/HO-1 and Akt/mTOR Pathways - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ali, Shakir; Bahcecioglu, Ibrahim H.; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2014)
Hepatocarcinogenesis is one of the most prevalent and lethal cancers. We studied the mechanisms underlying the inhibition of diethylnitrosamine (DEN)-induced hepatocarcinogenesis by lycopene in rats. Hepatocarcinogenesis was induced by an intraperitoneal injection of DEN followed by promotion with phenobarbital for 24 successive wk. The rats were given lycopene (20mg/kg body weight) 3times a week orally for 4 wk prior to initiation, and the treatment was continued for 24 consecutive wk. Lycopene reduced incidence, number, size, and volume of hepatic nodules. Serum alanine transaminase, aspartate aminotransferase, total bilirubin, and malondialdehyde (MDA) considerably increased and hepatic antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase) and glutathione decreased in DEN-treated rats when compared with the control group. Lycopene significantly reversed these biochemical changes and increased the expression of NF-E-2-related factor-2)/heme oxygenase-1, and it decreased NF-B/cyclooxygenase-2, inhibiting the inflammatory cascade and activating antioxidant signaling (P < 0.05). Lycopene also decreased DEN-induced increases in phosphorylated mammalian target of rapamycin (p-mTOR), phosphorylated p70 ribosomal protein S6 kinase 1, phosphorylated 4E-binding protein 1, and protein kinase B (P < 0.05). Lycopene is an active chemopreventive agent that offers protection against DEN-induced hepatocarcinogenesis by inhibiting NF-B and mTOR pathways.
Keywords: Nf-Kappa-B; Oxidative Stress; Hepatocellular-Carcinoma; Mediated Chemoprevention; Molecular Targets; Breast-Cancer; Inhibitor; Inflammation; Induction; Mechanisms